A MEMÓRIA DE CURTO PRAZO DO UNIVERSITÁRIO E A PRÁTICA DE JOGOS: UM ESTUDO EXPLORATÓRIO - Nunes, Oldemar (2010)
This study initially evaluates the short-term memory of University students, then the modalities of games by these students and the frequency with which these are practiced are verified, and finally the level of short-term memory observed is related to the playing of games. Our hypothesis is that the practice of playing games is influenced by the short-term memory. Term of Free and Informed Consent - TCLE (Annex A). We utilize the Pictorial Test of Memory - TEPIC-M from Rueda, F. J. M. and Sisto, F. F., duly validated for our reality, and the self-evaluative scale of the practice of leisure/sport games, which aims to determine the type of game played, whether of physical movement, logical reasoning or knowledge and digital games. The research is performed with 100 students of both genders. The results are analyzed by means of the Statistical Package for Social Sciences for Windows, SPSS, version 12.0. The short-term memory levels found were very low: Low (66%), Lower Average (25%), Average (2%), Higher Average (6%) and High (1%). The practice of playing games in their various modalities was also low in Movement Games - JM and Digital Games - JD (25%) and higher in Reasoning Games - JR (61%). The comparison between the results in the TEPIC-M and the frequency of participation in JM proved to be positive, since those who never practiced JM (74%) did not reach even the average level of memory; the same was observed regarding JD, with 70% of their participants who do not play these games without reaching the average level of memory; and, with relation to JR, a smaller percentage (44%) of those who do not play these games without reaching the average level of memory, data which indirectly confirm the hypothesis of this study.